Difference between revisions of "Quadratic formula"

m
m (Formatting)
 
(One intermediate revision by the same user not shown)
Line 1: Line 1:
 
The '''quadratic formula''' is a general [[expression]] for the [[root (polynomial)|solutions]] to a [[quadratic equation]]. It is used when other methods, such as [[completing the square]], [[factoring]], and [[square root property]] do not work or are too tedious.
 
The '''quadratic formula''' is a general [[expression]] for the [[root (polynomial)|solutions]] to a [[quadratic equation]]. It is used when other methods, such as [[completing the square]], [[factoring]], and [[square root property]] do not work or are too tedious.
  
===General Solution For A Quadratic by Completing the Square===
+
== Statement ==
 +
 
 +
For any quadratic equation <math>ax^2+bx+c=0</math>, the following equation holds.
 +
<cmath>x = \frac{-b \pm \sqrt{b^2-4ac}}{2a}</cmath>
 +
 
 +
=== Proof ===
 
We start with
 
We start with
  
 
<cmath>ax^{2}+bx+c=0</cmath>
 
<cmath>ax^{2}+bx+c=0</cmath>
  
Divide by <math>a</math>:
+
Dividing by <math>a</math>, we get
  
 
<cmath>x^{2}+\frac{b}{a}x+\frac{c}{a}=0</cmath>
 
<cmath>x^{2}+\frac{b}{a}x+\frac{c}{a}=0</cmath>
Line 31: Line 36:
  
 
This is the quadratic formula, and we are done.
 
This is the quadratic formula, and we are done.
 
===Video Solution by ligonmathkid2===
 
https://youtu.be/Akz8LcVGj5k
 
  
 
=== Variation ===
 
=== Variation ===
 
In some situations, it is preferable to use this variation of the quadratic formula:
 
In some situations, it is preferable to use this variation of the quadratic formula:
  
<cmath>\frac{2c}{-b\pm\sqrt{b^2-4ac}}</cmath>
+
<cmath>\frac{2c}{-b\mp\sqrt{b^2-4ac}}</cmath>
  
 
== See Also ==
 
== See Also ==
Line 45: Line 47:
 
[[Category:Algebra]]
 
[[Category:Algebra]]
 
[[Category:Quadratic equations]]
 
[[Category:Quadratic equations]]
 +
{{stub}}

Latest revision as of 09:11, 2 February 2025

The quadratic formula is a general expression for the solutions to a quadratic equation. It is used when other methods, such as completing the square, factoring, and square root property do not work or are too tedious.

Statement

For any quadratic equation $ax^2+bx+c=0$, the following equation holds. \[x = \frac{-b \pm \sqrt{b^2-4ac}}{2a}\]

Proof

We start with

\[ax^{2}+bx+c=0\]

Dividing by $a$, we get

\[x^{2}+\frac{b}{a}x+\frac{c}{a}=0\]

Add $\frac{b^{2}}{4a^{2}}$ to both sides in order to complete the square:

\[\left(x^{2}+\frac{b}{a}x+\frac{b^{2}}{4a^{2}}\right)+\frac{c}{a}=\frac{b^{2}}{4a^{2}}\]

Complete the square:

\[\left(x+\frac{b}{2a}\right)^{2}+\frac{c}{a}=\frac{b^{2}}{4a^{2}}\]

Move $\frac{c}{a}$ to the other side:

\[\left(x+\frac{b}{2a}\right)^{2}=\frac{b^{2}}{4a^{2}}-\frac{c}{a}=\frac{ab^{2}-4a^{2}c}{4a^{3}}=\frac{b^{2}-4ac}{4a^{2}}\]

Take the square root of both sides:

\[x+\frac{b}{2a}=\pm\sqrt{\frac{b^{2}-4ac}{4a^{2}}}=\frac{\pm\sqrt{b^{2}-4ac}}{2a}\]

Finally, move the $\frac{b}{2a}$ to the other side:

\[x=-\frac{b}{2a}+\frac{\pm\sqrt{b^{2}-4ac}}{2a}=\frac{-b\pm\sqrt{b^{2}-4ac}}{2a}\]

This is the quadratic formula, and we are done.

Variation

In some situations, it is preferable to use this variation of the quadratic formula:

\[\frac{2c}{-b\mp\sqrt{b^2-4ac}}\]

See Also

This article is a stub. Help us out by expanding it.